Covalent immobilization of ß-galactosidase on carrageenan coated with chitosan - Elnashar, Magdy; Yassin, M. (John Wiley and Sons Inc, 2009)
ß-Galactosidase was covalently immobilized to carrageenan coated with chitosan for the hydrolysis of lactose. The chitosan-carrageenan polyelectrolyte interaction was found to be dependent on the chitosan pH. At pH 4, the chitosan reached its maximum binding of 28.5% (w/w) where the chitosan surface density was 4.8 mg chitosan/cm2 g of carrageenan gel disks, using Muzzarelli method. Glutaraldehyde was used as a mediator to incorporate new functionality, aldehydic carbonyl group, to the bio-polymers for covalent attachment of bgalactosidase. The enzyme was covalently immobilized to the biopolymer at a concentration of 2.73 mg protein per g of wet gel. FTIR proved the incorporation of the aldehydic carbonyl group to the carrageenan coated with chitosan at 1720 cm-1. The optimum time for enzyme immobilization was found to be 16 h, after which a plateau was reached. The enzyme loading increased from 2.65 U/g (control gel) to 10.92 U/g gel using the covalent technique. The gel's modification has shown to improve the carrageenan gel thermal stability as well as the immobilized enzyme. For example, the carrageenan gel treated with chitosan showed an outstanding thermal stability at 95°C compared with 35°C for the untreated carrageenan gel. Similarly, the immobilization process shifted the enzyme's optimum temperature from 50°C for the free enzyme towards a wider temperature range 45-55 °C indicating that the enzyme structure is strengthened by immobilization. In brief, the newly developed immobilization method is simple; the carrier is cheap, yet effective and can be used for the immobilization of other enzymes. © 2009 Wiley Periodicals, Inc.